2021
DOI: 10.1038/s41563-020-00875-3
|View full text |Cite|
|
Sign up to set email alerts
|

Ferroelastic-switching-driven large shear strain and piezoelectricity in a hybrid ferroelectric

Abstract: Ferroelastic-switching-driven large shear strain and piezoelectricity in a hybrid ferroelectric

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 45 publications
0
96
0
Order By: Relevance
“…Nevertheless, multiferroic materials with the coexistence of ferroelectric and ferroelastic orders, especially those occurring at above room temperature, are very scarce. Very recently, Wang et al demonstrated interesting coupled ferroelasticity and ferroelectricity in a hexagonal perovskite system, 22 in which a ferroelastic switch with a large shear strain of up to 21.5% could be driven by an electric field and yield a recorded piezoelectric coefficient d 35 of up to 4800 pm V −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, multiferroic materials with the coexistence of ferroelectric and ferroelastic orders, especially those occurring at above room temperature, are very scarce. Very recently, Wang et al demonstrated interesting coupled ferroelasticity and ferroelectricity in a hexagonal perovskite system, 22 in which a ferroelastic switch with a large shear strain of up to 21.5% could be driven by an electric field and yield a recorded piezoelectric coefficient d 35 of up to 4800 pm V −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The mechanical properties of a material tell us a lot about its longevity, its ability to withstand damage, and its potential applications. 10 We are now in a period where shape-memory alloys, 11 flexible electronics, 12,13 ferroelastics, [14][15][16] and other mechanically-complex and exciting materials are becoming commonplace. As well this, modelling tools such as finite element analysis (FEA) often require prior knowledge of properties such as the Young's modulus to accurately predict the behaviour and performance of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic hybrids constitute a large family of molecular ferroelastics, exemplified by (ferrocenium)FeCl 4 (m3mFmmm), 71 (Me 3 NOH) 2 ZnCl 4 (mmmF2/m), 72 (3-chloro-2hydroxypropyltrimethylammonium) 2 CuCl 4 (432F32), 73 75 (homopiperazine-1,4-diium)[K(BF 4 ) 3 ] (m3mFmmm), 76 and [C 6 H 5 N(CH 3 ) 3 ]CdCl 3 (mm2Fm). 77 The (ferrocenium)(FeCl 4 ) salt is an interesting molecular semiconducting ferroelastic with a high T C (408 K) and a narrow band gap of 1.61 eV. 71 The [C 6 H 5 N(CH 3 ) 3 ]CdCl 3 complex is a hybrid ferroelectric and exhibits a huge shear strain (up to 21.5%), about two orders of magnitude larger than those of conventional ferroelectric oxides and polymers (Fig.…”
Section: Ferroelasticitymentioning
confidence: 99%